Adoptive T Cell Therapy for Epstein–Barr Virus Complications in Patients With Primary Immunodeficiency Disorders - McLaughlin, Lauren P.; Bollard, Catherine M.; Keller, Michael D. (Frontiers in Immunology, 2018)
Patients with Primary Immunodeficiency disorders (PID) have an increased risk from acute and chronic Epstein Barr Virus (EBV) viral infections and EBV-associated malignancies. Hematopoietic stem cell transplantation (HSCT) is a curative strategy for many patients with PID, but EBV-related complications are common in the immediate post-transplant period due to delayed reconstitution of T cell immunity. Adoptive T cell therapy with EBV-specific T cells is a promising therapeutic strategy for patients with PID both before and after HSCT. Here we review the methods used to manufacture EBV-specific T cells, the clinical outcomes and the ongoing challenges for future development of the strategy.